PENERAPAN PRINSIP TANGGUNG JAWAB KOPORAT DALAM PENEGAKAN HUKUM TERHADAP TINDAK PIDANA LINGKUNGAN OLEH PERUSAHAAN - Wijaya, Fatnuh; Prianda, Didit Nazar; Marwan (Jurnal Metrum, 2024)
As a gift from God Almighty, Indonesia's natural resources should be utilized as much as possible for the prosperity and welfare of the Indonesian people. For this reason, it is necessary and very important to create a balanced and just relationship between the conservation of natural resources and the utilization of these natural resources so that environmental pollution or destruction does not occur. This environmental problem is not only the responsibility of the government but also society and corporations are also responsible. Social Responsibility or more commonly known as CSR (Corporate Social Responsibility) is starting to be discussed by people nowadays. That business must continue to prioritize ethics and standards, not only in terms of administration but also compliance with internal rules. The research method used in this research is the library research method, which is an approach to conducting research that uses information sources found in libraries or other literary sources. The principles of corporate responsibility include accountability and transparency. This is what a company or business organization must then carry out. If the principles cannot be implemented by a company, it is very easy to commit criminal offenses, especially environmental crimes. The Company holds full responsibility for all environmental impact risks resulting from its operations.